ROOTING HUMAN RELATIONSHIPS: MENTAL HEALTH, OCCUPATIONAL THERAPY, AND THE NATURE-BASED PRACTICES - Silva, Gabriel Baptista e; Martins, Paula Andrea; Surjus, Luciana Togni de Lima e Silva (Seven Editora, 2025)
The relationship between humans and nature is the subject of numerous disciplines, perspectives, and worldviews, in which their interdependence is recognized. That is, human actions can exploit, alter, and devastate nature, just as the consequences of neglecting nature can jeopardize living conditions and human activities. The United Nations Environment Programme (UNEP) and the World Health Organization have pointed out that the planetary crisis of climate change impacts mental health due to economic and social losses, profoundly and enduringly affecting people’s well-being. The article proposed a dialogue between nature-based practices and Occupational Therapy, aiming to promote mental health by reconnecting people with nature and strengthening social relationships. The review results indicate that activities such as community gardening can improve the mental health of individuals experiencing stress, anxiety, and depression; interaction with nature and collaborative work can reduce the effects of social isolation, strengthening bonds and providing a sense of belonging and recognition, which are essential for psychological well-being. Occupational Therapy from an ecosocial perspective has strategically focused on the intersection of health, environment, and social inclusion, contributing to interventions that address unique needs and stimulate social and environmental changes, promoting resilient and inclusive communities. The university extension projects developed at Unifesp show promise for promoting mental health in an inseparable manner from social cohesion, inclusion, and sustainability. DOI: https://doi.org/10.56238/sevened2025.037-014